Transaction Cost Structure on Agribusiness System of Cassava in Lampung Province - Zulkarnain, Zulkarnain; Abbas Zakaria, Wan; Haryono, Dwi; Murniarti, Ktut; Irfan Affandi, Muhammad (Opción, 2019)
The high transaction costs often make the production process in cassava farming inefficient that the income received is not optimal. Transaction costs di- rectly reduce the income of the farmers, especially at the long harvest time and the risk of high price on cassava farming. Transaction costs are difficult to avoid, that it causes the economic pressure for the farmers due to the large surplus transfer from farmers to other parties. The research objective is to find out how much the transaction cost structure is which occurs in the process of cassava farming in Lampung Province. The research method used is a deep interview method for each interview activity. The analytical tool used in this study is transaction cost analysis. The population of Cluster I which located in Terusan Nunyai Sub district in this study were 854 farmers consisting of 473 cassava farmers in Bandar Agung Village, and 381 cassava farmers in Bandar Sakti Village. Mean while, the population of Cluster II which located in Rum- bia District is 1.712 farmers consisting of 951 cassava farmers in Ruki Basuki Village, and 761 cassava farmers in Bina Karya Putra Village. The sampling technique was obtained by doing the simple random sampling method. The number of samples at the study in Central Lampung Regency was 271 peo- ple. From the transaction cost structure research, it could be concluded that there are 2 (two) transaction fee structure scenarios in the cassava agribusi- ness system with an average farm size of 0,95 hectares, namely (a) transaction cost structure with farm financing of Rp. 795.525,44 and (b) transaction costs structure without farm financing of Rp. 625.222,68. The largest transaction costs for businesses was Rp. 431.134,88 (54,19% ) higher than transaction costs on financing (21,41%) and cassava selling (24,40%). This happens because farmers have to do farming planning, supplying farming inputs, and doing farm operations. One of the biggest components in transaction costs in the supply of cassava farming inputs is lost farmer income.